The Meaning of Learning Methods and Strategies in Islamic Education - Harlyan Nurpatimah; Abdul Latif; Maspuroh; Erga Tenang Lambang; Silviyawati (Penerbit Hellow Pustaka, 2025)
Islamic educational philosophy is essentially a concept of thinking about education that is sourced from or based on the teachings of Islam. The philosophy of Islamic education is a discussion of the essence of Muslims' ability to be fostered, developed, and guided, so that they become human beings whose whole person is imbued with Islamic teachings. Because the problem of education is so complex and the interpretation of philosophy is so complicated, it is necessary to have learning methods and strategies in Islamic education, as well as the characteristics that need to be understood about modern-contemporary learning strategies.